Analysis of the Symbolic Meaning of the Mande' Bedel Keraja' Traditional Ritual at the Pakunegara Palace, Tayan Hilir District - Kurniawan, Syafarani; Bahari, Yohanes; Wiyono, Hadi (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to describe the symbolic meanings in the initial, core, and final stages of the mande' bedel keraja' ritual at the Pakunegara Palace. The mande' bedel keraja' is an annual ritual of bathing the bedel', the heirloom weapon of the Tayan Palace, serving as a protective rite (tolak bala) to ward off disasters and safeguard the kingdom from calamities such as droughts and disease outbreaks. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, involving two main informants and two supporting informants. Data analysis included reduction, presentation, and conclusion drawing. The findings show that the initial stage involves parading the bedel' to Ujung Tanjung, accompanied by symbolic objects such as the bedel', ketubong drum, tepa, candles, umbrella, yellow scarf, and flags of yellow, white, red, and black. The core stage includes the mengkasai and melangir rituals, symbolized by rice, turmeric, kaffir lime, and melangir. The tepung tawar ceremony uses symbolic materials such as rice, jeringau (sweet flag), kencur (aromatic ginger), sabang hijau, goat’s foot leaves, ganda rusa, and puring. The final stage involves rinsing the bedel’, where the water symbolizes healing and fertility for a bountiful harvest. The ketupat war ritual represents resistance against misfortune and gratitude for agricultural abundance.